PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL COOPERATIF LEARNING TYPE SNOWBALL THROWING DALAM PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK KELAS XII DI SMAK SANTO MIKHAEL SOLOR - Yohanes Hego Mukin; Fransiska Aprilia Perada Goran (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to improve the learning outcomes of class XII Social Sciences students at SMAK Santo Mikhael Solor using the Cooperative Learning model type Snowball Throwing. The method used in this study is Classroom Action Research (CAR). This CAR is used by researchers to find out the problems that occur in the classroom and find solutions to overcome the problems that occur. The location was at SMAK Santo Mikhael Solor, Lewonama Village, West Solor District, East Flores Regency-NTT. The subjects were 22 class XII IIS students of 5 male students and 18 female students. Data collection techniques used were observation, interviews and tests. The results of the study were pre-cycle average outcome scores of 46.72, there were 2 students who completed with a percentage 9% while those who incomplete were 20 people with a percentage 91%. While cycle 1 there were 4 students who incomplete with a percentage 18% and those who complete were 18 students with a percentage 81%. And cycle 2 there were all students who complete with a percentage 100%. Thus, the use of the Cooperative Learning model type Snowball Throwing can improve the learning outcomes of students in class XII IIS SMAK Santo Mikhael Solor.